COMPARISION BETWEEN FOUR MAJOR BUSINESS EXCELLENCE ASSESSMENT FRAMEWORKS - Singh, Ajayjit (2011)
This research was carried out to make a comparison between four publically available Business Excellence Frameworks such as the Malcolm Baldrige National Quality Award (MBNQA), the European Foundation for Quality Management (EFQM), The Shingo Prize and the Lean Enterprise Self-Assessment Tool. The primary objective of the research was to analyse and compare the fundamental principles of each framework as well as the detailed and more “tangible” criteria sections and sub-sections of all the models to see if they are all fundamentally the same and if not, what the differences were. The overall result of this research pointed to the conclusion that all four models and thus all models that are based on these models all heavily draw from the principles of TQM, are fundamentally the same and all test the same criteria save for one essential difference. After the models were mapped onto each other, a quick assessment was conducted of Hill & Smith Holdings PLC using the LESAT V1.0 Self – Assessment Tool. LESAT V1.0 was used due to its standardized nature that allowed for the quickest coverage of all criteria items. Post-assessment, the scores from the LESAT model were transposed onto the other models leading to another finding that all models give somewhat the same scores for the same organization.